Endophytic bacterium CIMAP-A7 mediated amelioration of atrazine induced phyto-toxicity in Andrographis paniculata. (15th October 2021) - Tripathi, Pratibha; Yadav, Ranu; Das, Paurabi; Singh, Asha; Singh, Raghavendra Pratap; Kandasamy, Premalatha; Kalra, Alok; Khare, Puja
Abstract: The presence of atrazine, a triazine herbicide, and its residues in agriculture soil poses a serious threat to human health and environment through accumulation in edible plant parts. Hence, the present study focused on atrazine induced stress amelioration of Andrographis paniculata, an important medicinal plant, by a plant growth promoting and atrazine degrading endophytic bacterium CIMAP-A7 inoculation. Atrazine has a non-significant effect at a lower dose while at a higher dose (lower: 25 and higher: 50 mg kg −1 ) 22 and 36% decrease in secondary metabolite content and plant dry weight of A. paniculata was recorded, respectively. Endophyte CIMAP-A7 inoculation significantly reduced atrazine soil content, by 78 and 51% at lower and a higher doses respectively, than their respective control treatments. Inoculation of CIMAP-A7 exhibited better plant growth in terms of increased total chlorophyll, carotenoid, protein, and metabolite content with reduced atrazine content under both atrazine contaminated and un-contaminated treatments. Atrazine induced oxidative stress in A. paniculata was also ameliorated by CIMAP-A7 by reducing stress enzymes, proline, and malondialdehyde accumulation under contaminated soil conditions than un-inoculated treatments. Furthermore, the presence of atrazine metabolites deisopropylatrazine (DIA) and desethylatrazine (DEA) strongly suggests a role of CIMAP-A7 in mineralization however, the absence of these metabolites in uninoculated soil and all plant samples were recorded. These findings advocate that the amelioration of atrazine induced stress with no/least pesticide content in plant tissues by plant-endophyte co-interactions would be efficient in the remediation of atrazine contaminated soils and ensure safe crop produce. Graphical abstract: Image 1 Highlights: Mineralization of atrazine by an endophytic bacterial strain CIMAP-A7 was explored. Endophyte mediated reduced atrazine stress in a plant-soil system was deciphered. CIMAP-A7 inoculation showed PGP along with no or less atrazine content in leaves of A. paniculata . CIMAP-A7 inoculation limits atrazine soil content by 78 and 51% at 25 and 50 mg kg −1 dose respectively. Atrazine metabolites DEA and DIA were also detected in soil of CIMAP-A7 inoculated treatments. Abstract : Endophyte (CIMAP-A7) has a potential to restrict the atrazine accumulation in plant and catalyze its mineralization.